دراسة تجريبية لمختلف رمال البناء المستخدمة في منطقة الجنوب الشرقي من الجزائر - عامر زهري, زهري; عبد القادر, رحموني; ناجي, الهامل (University of El-Oued, 2021)
"The eastern region (Wadi Suf and Wadi Rig) is characterized by the multiplicity of sand intended for construction and concrete works, and these sands differ in terms of physical and chemical properties, which has become a problem in choosing the most appropriate and quality sand for construction workshops, as the subject of our study revolves around this framework, as it is an experimental study trail of different types of Building Sand which located in El Oued and Ouedi Righ, the southeast of Algeria. From this area, we chose seven (7) types of sand; the yellow and red sand at Djamaa, the sand of Al-Baaj, El Assila, El Barkajia in El Meghaier, as well as the sands of Sidi Sliman and Meger at Touggourt. In the other hand, we prepared seven (7) types of Mortar (masonry) with two (2) types of Tile (or cement) (Sulfate-resistant Cement and Ordinary) and reduced them in two different mediums (he rising water and ordinary water) in the Wed Righ region (Djamaa) in order to study the mechanical resistance and permanence, The aim of this study is to make a practical evaluation of the effect of different sand types on the mechanical behavior of mortar. From the results we obtained, we found some differences between the types of sand used, some of which are close and some of which are far apart. Through this study, we also found that the most studied sand is usable regarding the construction, except for El Barkajia sand, which it considers to be heterogeneous sand in its composition and not ideal. " "تتميز المنطقة الشرقية (وادي سوف واودي ريغ ) بتعدد الرمال الموجهة لأعمال البناء والخرسانة وتختلف هذه الرمال من حيث الخصائص الفيزيائية والكميائية، مما أصبح يطرح إشكالاً في إختيار أنسب الرمال و أجودها لورشات البناء، حيث يتمحور موضوع درستنا حول هذا الإطار فهو عبارة عن دراسة تجريبية لمختلف أنوع رمل البناء المتواجدة في منطقة واد سوف واود ريغ بالجنوب الشرقي للجزائر وقد اخترنا من هذه المنطقة سبع أنواع من الرمال (الرمل الأصفر والأحمر بجامعة، رمل البعاج والعسيلة والبرقاجية بالمغير، ومن تقرت إخترنا رمل سيدي سليمان ومقر ) حيث قمنا بدراسة الخصائص الفيزيائية لهاته الرمال، كما حضرنا سبع أنواع من الملاط بنوعين من الإسمنت (اسمنت مقاوم للكبريتات واسمنت عادي) وحفظناها في وسطين مختلفين (ماء صاعد وماء عادي) في منطقة واد ريغ (جامعة) وذلك من أجل دراسة المقاومة الميكانيكة والديمومة. والهدف من هذه الدراسة هو إجراء تقييم تجريبي لتأثير مختلف رمال البناء على السلوك المكانيكي للملاط. ومن النتائج التي تحصلنا عليها وجدنا بعض الإختلافات بين أنواع الرمل المستعملة فمنها ما هو متقارب ومنها من هو متباعد. ومن خلال الدراسة كذلك تبين لنا أن جل الرمال المدروسة قابلة للإستعمال في مجال البناء عدا رمل البرقاجية الذي نعتبره رمل غير متجانس في تركيبته وغير مثالي. "
Matéreaux en génie civil مذكرة ماستر تخصص
Keywords: Sand - Physical Properties - Sulfate-resistant Cement - Tile (Cement) - Permanence - Rising Water - Mechanical Resistance.; رمل البنـــــــاء – الخصائص الفيزيائية - اسمنت مقاوم للكبريتات -ملاط الاسمــــنت – الديمومـــــــة – المياه الصاعـــــــدة – المقاومــــــــــة الميكانيكية.